INFARK MIOKARD VENTRIKEL KANAN - Arga Putra Mangitung, Muhammad; Laksono, Sidhi (Universitas Ciputra Surabaya, 2024)
Right ventricular myocardial infarction (RVMI) is a serious complication of myocardial infarction, in particular inferior infarction. This condition is characterized by impaired blood flow to the right ventricle resulting in ventriculary dysfunction and hemodynamic disorders. Diagnosis of RVMI requires clinical examination, electrocardiography, and echocardiography. The primary management of RVMI is revascularization as soon as possible to restore blood flow and improve ventricular function. The prognosis of RVMI depends on the location and extent of the infarction, with the blockage of the right marginal artery of the proximal artery having a worse prognosis.